Professor Piotr PERZYNA - PĘCHERSKI, Ryszard (Engineering Transactions, 2014)
This issue is dedicated to the memory of Professor Piotr Perzyna, the one of creators of viscoplasticity theory, a specialist in problems of solid mechanics, thermodynamics of materials, wave propagation and damage dynamics. For many of us he was a teacher, mentor, and friend, who shared his experience and competence as a member of the Engineering Transactions Editorial Board. Professor Piotr Perzyna also published original scientific papers and critical reviews in the Journal. With this collection of scientific papers we wish to pay our tribute to the memory of Professor Piotr Perzyna. A comprehensive account of his life and scientific activity was presented in earlier issue of Engineering Transactions (61, 3, 167–171, 2013). The list of his most important scientific papers and books is given on the website: http://www.perzyna.put.poznan.pl/ of Poznan University of Technology, where Professor Piotr Perzyna was awarded the Doctor Honoris Causa title.